2011 19th International Euromicro Conference on Parallel, Distributed and Network-Based Processing 2011
DOI: 10.1109/pdp.2011.92
|View full text |Cite
|
Sign up to set email alerts
|

Scaleable Sparse Matrix-Vector Multiplication with Functional Memory and GPUs

Abstract: Sparse matrix-vector multiplication on GPUs faces to a serious problem when the vector length is too large to be stored in GPU's device memory. To solve this problem, we propose a novel software-hardware hybrid method for a heterogeneous system with GPUs and functional memory modules connected by PCI express. The functional memory contains huge capacity of memory and provides scatter/gather operations. We perform some preliminary evaluation for the proposed method with using a sparse matrix benchmark collectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Figure 7 shows the effective bandwidth of vector accesses during the execution of sparse matrices-vector double precision multiplication with two kinds of sparse matrix storage formats. The storage formats are the CRS and our format for GPUs [5]. As far as this experiment, we do not observe big difference in the two matrix storage formats.…”
Section: Sparse Matrices-vector Multiplication Access Bandwidthmentioning
confidence: 56%
See 3 more Smart Citations
“…Figure 7 shows the effective bandwidth of vector accesses during the execution of sparse matrices-vector double precision multiplication with two kinds of sparse matrix storage formats. The storage formats are the CRS and our format for GPUs [5]. As far as this experiment, we do not observe big difference in the two matrix storage formats.…”
Section: Sparse Matrices-vector Multiplication Access Bandwidthmentioning
confidence: 56%
“…For the evaluation of GPUs experiments, we use address trace data to which we apply the pre-processing algorithm [5] for the proposed extended memory and GPUs.…”
Section: (3) Accessing Vectors In Sparse Matrix-vector Multiplicationmentioning
confidence: 99%
See 2 more Smart Citations
“…This is more logical, as the data needed to solve the system of equation is generated and already resides in the GPU memory, and no transfer cost is to be needed. of SpMV kernels on graphics hardware has been the subject of many recent researches [23][24][25][26][27][28][29][30][31][32][33]. It has been shown that the naïve implementation of SpMV kernel is quite ineffective on such platforms [23].…”
Section: Solution Of Implicit Pressure Equationmentioning
confidence: 99%